On the differential impact of the recent economic downturn on work safety by nativity: The Spanish experience - Catalina Amuedo-Dorantes; Cristina Borra (IZA Journal of Migration, 2013)
This paper explores differences in work injury and fatality rates between immigrants and natives and how they may have been impacted by the recent economic downturn. Our focus is on Spain over the 2001-2010 decade -a period of time during which Spain received one of the largest immigrant inflows of any developed economy and subsequently experienced a recession that has raised national unemployment rates above 20 percent. We find that immigrants worked in riskier jobs than natives during this high immigration period. Furthermore, the recession appears to have exclusively reduced job injury rates, but not fatality rates, among the average immigrant -hinting on their misreporting due to fear of dismissal as the primary cause for the observed decline. Overall, the figures are suggestive of work safety inequalities that may be important to address.
Keywords: J61; J81; 330; working safety; injuries; fatalities; immigration; great recession; Spain